Identifying Students’ Scientific Literacy Needs: A Foundation for Developing a Problem-Based Global Warming Physics Module - Geby Anita; Ahmad Amin; Yaspin Yolanda (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2026)
Global warming has become a critical issue that requires younger generations to possess strong scientific literacy. However, various studies indicate that students’ understanding of scientific concepts and environmental phenomena remains limited. This pre-development study aims to identify students’ initial scientific literacy needs as a foundation for developing a problem-based learning module on global warming. This qualitative research involved 36 tenth-grade students of SMA Negeri 2 Lubuklinggau and employed interviews, observations, and Focus Group Discussions (FGD) with teachers. Data were analyzed using descriptive qualitative techniques, including data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation and member checking. The findings reveal that many students experience difficulties in interpreting scientific data, connecting physics concepts with real environmental phenomena, and drawing evidence-based conclusions. In addition, teachers emphasized the need for interactive and contextually relevant learning modules. These findings highlight the importance of needs analysis as a fundamental step in developing learning modules that not only convey concepts but also enhance students’ scientific literacy and scientific thinking skills.